Food as a Method of Placemaking for Latin American Immigrants in the US South: An Case Study of a Neighborhood in South Nashville, TN - Justin Luckner (The Journal for Undergraduate Ethnography)
Diverse groups of immigrants from Latin American countries populate modern-day Nashville like many other urban areas in the US South. Since the 1990s, immigrants from Mexico and other Latin American countries have migrated in high numbers to the region, leading to the creation of terms like “Nuevo South.” In Nashville, Latinx immigrants have culturally expressed themselves through food and food institutions have acted as impetus for a sense of community. International grocery stores and cultural restaurants not only act as mediums to spread and establish a sense of culture, but also as places for communities to form and learn from one another while integrating into a new environment. This paper will examine existing literature on the recent influx of immigration to the US South and the expression of culture via food in immigrant neighborhoods. This paper will employ Karen O’Reilly’s 2012 definition of participant observation ethnographies and Mark Wyckoff’s 2014 definition of placemaking to analyze immigrant-owned restaurants and grocery stores along Nolensville Pike in South Nashville as places of community. This paper seeks to prove that these food institutions constitute vital methods of placemaking for immigrants in the US South.